Review of Instructional Digital Media to Path Teachers’ Digital Competence on Philosophical Perspective: Distraction or Diversion - Ismail, Syofianis; Ling, Zhang; Nawir, Erna; Alber, Alber; Fauziah, Desna (Lafadz Jaya Publisher, 2023)
In spite of its emergence in 1980s, digital media has been well known to this day, yet it is still questioned whether its presence is merely a